1991
DOI: 10.1111/j.1423-0410.1991.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Dose Intravenous IgG for the Treatment of Severe Rhesus Alloimmunization

Abstract: The value of intravenous immunoglobulin (IVIG) in the treatment of 24 severely Rh-sensitized pregnant women was studied. IVIG was infused at a daily dose of 0.4 g/kg maternal body weight for 4-5 consecutive days, and was administered again 15-21 days later until delivery, depending on the evolution of the hemolytic disease. Our population was divided into 3 groups according to the time of onset of therapy: group 1 (n = 8), before 20 weeks' gestation; group 2 (n = 7), 20-28 weeks, and group 3 (n = 9), after 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…4 g/kg) prevents severe RhD-HD, although this finding was complicated by the additional use of maternal plasma exchange (Berlin et al, 1985;Besalduch et al, 1991). In contrast, two studies have shown the effectiveness of high-dose IVIgG alone when administered consecutively for 4-5 d, every 2 weeks (de la Camera et al, 1988) and particularly when initiated before 28 weeks gestation to severely affected neonates in the absence of hydrops fetalis (Margulies et al, 1991). A total of 100 g IVIgG given over 5-6 consecutive days, starting at 22 weeks gestation and repeated after 6 weeks, was also successful in maintaining higher fetal haemoglobin levels when compared to a control group (Gottvall & Selbing, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 g/kg) prevents severe RhD-HD, although this finding was complicated by the additional use of maternal plasma exchange (Berlin et al, 1985;Besalduch et al, 1991). In contrast, two studies have shown the effectiveness of high-dose IVIgG alone when administered consecutively for 4-5 d, every 2 weeks (de la Camera et al, 1988) and particularly when initiated before 28 weeks gestation to severely affected neonates in the absence of hydrops fetalis (Margulies et al, 1991). A total of 100 g IVIgG given over 5-6 consecutive days, starting at 22 weeks gestation and repeated after 6 weeks, was also successful in maintaining higher fetal haemoglobin levels when compared to a control group (Gottvall & Selbing, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mode of action of IVIgG in HD is not fully understood, it may significantly reduce the levels of maternal anti-D IgG (Bowman, 1990;Margulies et al, 1991). This may occur by direct inhibition of maternal immunoglobulin synthesis (de la Camera et al, 1988) possibly by enhancing T suppresser cell functions (Delfraissy et al, 1985) or from the high plasma IgG levels increasing the fractional catabolic rate of IgG and eliminating alloimmune antibody (Masson, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case series and case reports indicate a beneficial role of IVIG, at least in delaying the development of significant anemia [36]. Admittedly, focusing on the reported cases in the literature, the administration of IVIG varied considerably and was inadequate due to low doses, delayed administration (after fetal anemia was already present), and/or inconsequent administration in a number of cases (table 2) [30,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. Only one study has shown that the administration of 1 g/kg/week in four women with anti-D did not appear to improve outcomes of affected fetuses [58].…”
Section: Discussionmentioning
confidence: 99%
“…Although case reports, case series, an uncontrolled prospective trial, and a retrospective trial appear to reveal benefits from IVIG, prospective controlled trials are needed before this therapy can be recommended routinely[ 61, 62]. …”
Section: Indications With Substantial Evidence For Use As a First-linmentioning
confidence: 99%